Assessing the Environmental Impact of the Self-propelled Bulk Carriage through LCA - Hegedić, Miro; Štefanić, Nedeljko; Nikšić, Mladen (Promet - Traffic&Transportation, 2018)
Environmental sustainability of the transport sector is a highly important issue today. The European Commission has made a goal of delivering a minimum 60% reduction in greenhouse gas emissions from transport by 2050. Part of this reduction will come from the railway sector by making the maintenance processes more environmentally friendly. This paper presents the results of the environmental assessment of the self-propelled bulk carriage (SPBC), an innovative new product aiming to decrease the environmental impact of the railway maintenance processes. The life cycle assessment (LCA) methodology was used in the study, and environmental impact is given in five impact categories based on the CML 2001 method through three main modules of the self-propelled bulk carriage life cycle: upstream, core, and downstream. The novelty of the research includes the fact that this is the first life cycle assessment study done for the bulk carriage, as well in that the authors have proposed the use of a new functional unit in the category of freight railway vehicles. The biggest environmental impact of the self-propelled bulk carriage across all five categories is in the use and maintenance phase of its life cycle and mainly due to diesel fuel use. The SPBC uses significantly less fuel than a conventional diesel locomotive.